Heart rate and performance parameters in elite cyclists: a longitudinal study - Lucia, A.; Hoyos, J.; Perez, M.; Chicharro, J. L. (Medicine & Science in Sports & Exercise, 2000)
Purpose: This study was designed to evaluate the stability of target heart rate (HR) values corresponding to performance markers such as lactate threshold (LT) and the first and second ventilatory thresholds (VT1, VT2) in a group of 13 professional road cyclists (O2max 75.0 mL·kg-1·min-1) during the course of a complete sports season.